Telomere length and genetic variations affecting telomere length as biomarkers for facial regeneration with platelet‐rich fibrin based on the low‐speed centrifugation concept. (15th May 2018) - Nacopoulos, Cleopatra; Gkouskou, Kalliopi; Karypidis, Dimitrios; Vlastos, Ioannis; Vesala, Anna‐Maria; Choukroun, Joseph; Miron, Richard J; Prokopakis, Emmanuel
Summary: Background: Platelet‐Rich Fibrin (PRF), a fibrin matrix produced by single blood centrifugation that contains leukocytes, platelets, and growth factors, is increasingly being utilized for facial regeneration purposes. However, our understanding of the involved pathophysiological mechanisms affecting regeneration is limited and current protocols require better optimization. Biomarkers that are related to skin aging such as telomere length (TL) have been proposed as a mean to analyze patients' stratification. Objective: Our aim is to study whether the outcomes of a facial regeneration protocol performed with PRF are related to TL and genetic variations affecting TL. This can aid in the standardization of a surgical aesthetic protocol. Patients and Methods: In all, 41 patients treated with PRF produced with the low‐speed centrifugation concept were included in this observational study. The correlation between TL and genetic variations were assessed versus treatment outcomes, namely the number of sessions and aesthetic results utilizing the FACE‐Q skin satisfaction questionnaire. Results: In all, 39 of the 41 patients completed the treatment. TL correlated with the initial responses to FACE‐Q (ρ = .33, P = .05). Genetic variations affecting TL was related to the change of FACE‐Q (ρ = .35, P = .034) as well as to the number of treatment sessions (ρ = .38, P = .019). Conclusions: Telomere length (TL) was related to patient perceived facial skin appearance. In addition, genetic variations affecting TL were related to the final outcomes (number of sessions and improvements of FACE‐Q results) and may be a useful biomarker for future regenerative procedures performed with PRF for facial regeneration.